HUMAN IMPACT ON WATER REGIME OF THE SHARDARA WATER RESERVOIR - Issina Botagoz; J. Abuduwaili; S. Bissenbayeva; G.T. Issanova; A. Massakbayeva (Scientific Journal of Pedagogy and Economics, 2019)
Under rapid population growth, food demand and other human activities, water availability is predominantly becoming a common problem worldwide. This study considers Shardara water reservoir located on the Syrdarya River within Kazakhstan and investigates changes on its water regimes under human activities. The MannKendall trend test was used to explore the contributions of human activities to changes in inflow and discharge in Shardara water reservoir between 1980 and 2016. The results indicated that human activities, particularly agriculture and power generation activities are the major governing factors of changes on water regimes of the reservoir. The findings also indicated that, at significance level inflow and outflow of reservoir have positive trend. The inflow and discharge fluctuation of water often leads to serious floods in settlements at lower reaches of Syrdarya River accompanied by severe socio-economic damages and losses.